(untitled) - Selinger, Ben (Siney, Australia, 1996)
This edition includes a section on the naming of organic chemiacals, so that the reader can appreciate that there is a logic in those horrible chemicals name that is no worse than in other language such as Latin or Basic,...
Keywords: Chemistry,Chemistry; Popular works